1991
DOI: 10.1182/blood.v77.12.2764.bloodjournal77122764
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the paroxysmal nocturnal hemoglobinuria phenotype in normal human erythrocytes: effects of 2-aminoethylisothiouronium bromide on membrane proteins that regulate complement

Abstract: To investigate the mechanism by which treatment of normal human erythrocytes with the sulfhydryl reagent 2-aminoethylisothiouronium bromide (AET) induces susceptibility to complement mediated lysis, the effects of AET on the structural and functional integrity of decay accelerating factor (DAF), membrane inhibitor of reactive lysis (MIRL), and complement receptor type 1 (CR1) were examined. Following treatment with AET, erythrocyte MIRL and CR1 were no longer recognized in situ by antibodies, and antibody bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…The absence of these regulators is linked to complement-mediated lysis of erythrocytes in these patients. FH and FH-inspired candidate therapeutics protect erythrocytes from PNH patients ( 25 ), as well as erythrocytes that have been stripped of GPI-linked proteins and rendered “PNH-like” by treatment with 2-aminoethylisothiouronium bromide ( 39 ). We demonstrated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of these regulators is linked to complement-mediated lysis of erythrocytes in these patients. FH and FH-inspired candidate therapeutics protect erythrocytes from PNH patients ( 25 ), as well as erythrocytes that have been stripped of GPI-linked proteins and rendered “PNH-like” by treatment with 2-aminoethylisothiouronium bromide ( 39 ). We demonstrated ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Human erythrocytes lacking GPI-linked proteins (PNH-like) were prepared according to a modified version of the method of Ezzell et al ( 39 ). Whole human blood was obtained by phlebotomy and stored in Alsever’s solution (4°C).…”
Section: Methodsmentioning
confidence: 99%
“…The involvement of C3 suggested that erythrocyte CR1 participates in the IA reaction. To test this, erythrocytes were treated with AET (29) or trypsin (30), which destroy or inactivate CR1. In previous studies we confirmed (data not shown), that erythrocyte CR1 recognition by rabbit anti-CR1–specific antiserum (R137) decays in parallel to erythrocyte incubation time with AET, and that AET-treated erythrocytes no longer bind opsonized promastigotes; again, after AET or trypsin treatment, no IA reaction was observed (Table I).…”
Section: Resultsmentioning
confidence: 99%
“…In the present report, we evaluated the potency of anti-T haemolysins in vitro by comparing the levels of haemolysis produced by anti-T antibodies against T-activated RBCs, with those produced by anti-A and anti-B antibodies against group A1 and group B RBCs, respectively. To improve the detection of haemolysins, we used RBCs treated with 2-aminoethylisothiouronium bromide (AET), a sulphydryl reagent that partially or completely inactivates membrane complement regulatory proteins CD55 and CD59, respectively [12]. Using this sensitive haemolysis assay, anti-T haemolysins were found in sera of most blood donors but with lower activity compared with anti-A and anti-B antibodies.…”
Section: Introductionmentioning
confidence: 99%